Identification of flutter parameters for a wing model - De Marqui Junior,Carlos (2006)
A flexible mounting system has been developed for flutter tests with rigid wings in wind tunnel. The two-degree-of-freedom flutter obtained with this experimental system can be described as the combination of structural bending and torsion vibration modes. Active control schemes for flutter suppression, using a trailing edge flap as actuator, can be tested using this experimental setup. Previously to the development of the control scheme, dynamic and aeroelastic characteristics of the system must be investigated. Experimental modal analysis is performed and modes shape and frequencies are determined. Then, wind tunnel tests are performed to characterize the flutter phenomenon, determining critical flutter speed and frequency. Frequency response functions are also obtained for the range of velocities below the critical one showing the evolution of pitch and plunge modes and the coupling tendency with increasing velocity. Pitch and plunge data obtained in the time domain during these tests are used to evaluate the ability of the Extended Eigensystem Realization Algorithm to identify flutter parameter with increasing velocity. The results of the identification process are demonstrated in terms of the evolution of frequency and damping of the modes involved in flutter.